Immunoreactive Cu-SOD and Mn-SOD in lymphocytes sub-populations from normal and trisomy 21 subjects according to age - Baeteman, M A; Baret, A; Courtière, A; Rebuffel, P; Mattei, J F (Life sciences (1973), 1983)
Copper and manganese superoxide dismutases (Cu-SOD and Mn-SOD) were measured by radioimmunoassay in B and T lymphocytes and macrophages, in patients with trisomy 21 and in matched controls. In the controls, Cu-SOD was present in greater amounts than Mn-SOD and there were quantitative differences in the distribution in the three cellular sub-populations. In trisomy 21, levels of Cu-SOD were raised, with no change in levels of Mn-SOD, supporting the theory of a gene dosage effect. There were significant positive and negative correlations between age and Cu-SOD levels in controls, and a correlation approaching significance for Mn-SOD. In trisomy 21, there was no correlation between age and Cu-SOD levels, and the only significant correlation for Mn-SOD was for B lymphocytes.